Fickian yet non-Gaussian behaviour: A dominant role of the intermittent dynamics - Acharya, Sayantan; Nandi, Ujjwal Kumar; Bhattacharyya, Sarika Maitra (Journal Of Chemical Physics, 2017)
We present a study of the dynamics of small solute particles in a solvent medium where the solute is much smaller in size, mimicking the diffusion of small particles in crowded environment. The solute exhibits Fickian diffusion arising from non-Gaussian Van Hove correlation function. Our study shows that there are at least two possible origins of this non-Gaussian behaviour: the decoupling of the solute-solvent dynamics and the intermittency in the solute motion, the latter playing a dominant role. In the former scenario when averaged over time long enough to explore different solvent environments, the dynamics recovers the Gaussian nature. In the case of intermittent dynamics the non-Gaussianity remains even after long averaging and the Gaussian behaviour is obtained at a much longer time. Our study further shows that only for an intermediate attractive solute-solvent interaction the dynamics of the solute is intermittent. The intermittency disappears for weaker or stronger attractions. Published by AIP Publishing.

Fickian yet non-Gaussian behaviour: A dominant role of the intermittent dynamics (vol 146, 134504, 2017) - Acharya, Sayantan; Nandi, Ujjwal Kumar; Bhattacharyya, Sarika Maitra (Journal of Chemical Physics, 2019)